Brazil and Climate Justice : Pioneering Climate Litigation for a Global Cause - Carvalho, Délton Winter de,; Rocha, Armando,; Tigre, Maria Antonia, (International Environmental Law ;, 2025)
The stakes of climate change in Brazil extend far beyond its borders, influencing global biodiversity, the Amazon rainforest, and planetary climate stability. With the fourth-highest number of climate cases worldwide and a leadership role in the Global South, Brazil stands at the forefront of the global climate justice movement. This edited volume delves into nearly 90 groundbreaking cases, uncovering innovative legal strategies and their profound implications for international climate policies. Highlighting Brazil's unique ecological importance, particularly the Amazon's role in sustaining global balance, the book features contributions from leading scholars and litigators. This indispensable resource offers critical insights and inspires creative legal pathways to tackle the world's most pressing climate challenges.